Optimal Frequency Range Selection for PZT Transducers in Impedance-Based SHM Systems - Baptista, Fabricio Guimaraes [UNESP]; Vieira Filho, Jozué [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Piezoelectric transducers of PZT (lead zirconate titanate) have been widely used in structural health monitoring (SHM) systems based on the electromechanical (E/M) impedance technique. In this technique, damages in the structure are identified by measuring the electrical impedance of the transducer in an appropriate frequency range. Usually, the selection of the correct frequency range to detect and evaluate damage is obtained by trial and error methods. In this paper, it is proposed a formal procedure to determine the frequency ranges in which the PZT transducers are more sensitive for damage detection. Tests were carried out on specimens with different sizes and there was a good match between the theoretical and practical results.
Keywords: Frequency; impedance; lead zirconate titanate (PZT) ceramics; structural engineering